Design, synthesis, and pharmacological evaluation of fluorinated azoles as anti-tubercular agents - Gholap, Somnath; Tambe, Macchindra; Nawale, Laxman; Sarkar, Dhiman; Sangshetti, Jaiprakash; Damale, Manoj (Archiv Der Pharmazie, 2018)
Design, synthesis, and biological screening of 2,2-dimethyl-2,3-dihydrobenzofuran tethered 1,3,4-oxadiazole derivatives as anti-tubercular agents were described. The synthesis of the target compounds was conducted by a series of reaction schemes. All the synthesized compounds were characterized by IR, H-1 NMR, C-13 NMR, and mass spectrometry. The therapeutic potential of the synthesized compounds was confirmed by molecular docking studies. Among the synthesized compounds, 12a, 12c, 12d, 12e, 12g, and 12j were found to be more active against non-replicating than against replicating cultures of Mycobacterium tuberculosis H37Ra ex vivo and in vitro. These compounds exhibit minimum inhibitory concentration (MIC) values in the range of 2.31-23.91g/mL. The cytotoxicity study was conducted against the cell lines THP-1, A549 and PANC-1, and the compounds were observed to be non-toxic to host cells. Molecular docking was conducted with InhA (FabI/ENR) and suggested the antimycobacterial potential of the synthesized compounds. The investigation presented here was found to be adventitious for the development of new therapeutic agents against Mycobacterium infection.
Keywords: 1; 2; 2-dimethyl-2; 3; 3-dihydrobenzofuran; 4-Oxadiazole; anti-tubercular agents; Cytotoxicity; Molecular docking